2016
DOI: 10.1016/j.chembiol.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase LSD1 Promotes Adipocyte Differentiation through Repressing Wnt Signaling

Abstract: Adipose tissue plays important roles in animals. White fat stores energy in lipids, while brown fat is responsible for nonshivering thermogenesis through UCP1-mediated energy dissipation. Although epigenetic mechanisms modulate differentiation in multiple lineages, the epigenetic regulation of brown adipocyte differentiation is poorly understood. By screening a collection of epigenetic compounds, we found that Lysine-Specific Demethylase 1 (LSD1) inhibitors repress brown adipocyte differentiation. RNAi-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 63 publications
(75 reference statements)
2
35
0
Order By: Relevance
“…Overexpression of LSD1 in BMSCs blocked Wnt signaling pathway by demethylating H3K4 and epigenetically silencing pro‐osteogenic Wnt‐gene promoters (Fig. ) . In addition, knockdown of LSD1 or its partner REST corepressor 2 (rcor2) blocked adipogenesis and increased expression of inflammatory cytokines and chemokines in 3T3‐L1 preadipocytes .…”
Section: Epigenetic Contributions To the Osteo‐adipogenic Switch Of Bmentioning
confidence: 89%
See 2 more Smart Citations
“…Overexpression of LSD1 in BMSCs blocked Wnt signaling pathway by demethylating H3K4 and epigenetically silencing pro‐osteogenic Wnt‐gene promoters (Fig. ) . In addition, knockdown of LSD1 or its partner REST corepressor 2 (rcor2) blocked adipogenesis and increased expression of inflammatory cytokines and chemokines in 3T3‐L1 preadipocytes .…”
Section: Epigenetic Contributions To the Osteo‐adipogenic Switch Of Bmentioning
confidence: 89%
“…LSD1 has also been identified as a key epigenetic regulator in brown adipogenesis, and inhibition or depletion of LSD1 repressed brown adipocyte tissue differentiation in vitro and in vivo . Knockdown of LSD1 decreased differentiation of 3T3‐L1 preadipocytes.…”
Section: Epigenetic Contributions To the Osteo‐adipogenic Switch Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…LSD1 forms a complex with PRDM16 and C‐terminal binding proteins 1 and 2 to repress WAT‐specific gene expression in BAT (17). In addition, LSD1 promotes both white and brown adipocyte differentiation by suppressing Wnt signaling in mesenchymal stem cells (36). In this study, we found that LSD2 positively regulates BAT‐associated genes while repressing myogenic genes depending on the derivation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, KDM1A demethylates H3K4me1/me2 at promoter regions of Wnt-pathway target genes, activating their expression and promoting brown adipogenesis [37].…”
Section: Kdm1a and Cellular Differentiationmentioning
confidence: 99%